Understanding The Concept Of Grants And Alms From A Syariah Economic Perspective - Dinda Marshanda; Sophia Nazwa; Muhammad Nur Iqbal (Jurnal Multidisiplin Sahombu, 2025)
Grants and alms are two important concepts in muamalah jurisprudence that have social and spiritual dimensions. From the perspective of muamalah jurisprudence , both are forms of non-commercial transactions based on the principle of voluntary ( tabarru ' ) and aim to get closer to Allah and strengthen social relations. This study uses a library study method with a qualitative approach, analyzing primary and secondary sources in Islamic literature. The main sources include books and Fiqh books. The results of the study show that grants and alms have similarities in the nature of being willing and based on the sincerity of the giver. However, there are fundamental differences in terms of purpose and recipient. Grants are general in nature and can be given to anyone without regard to the economic conditions of the recipient. In contrast, alms are intended to help those in need and are often a means of worship for the giver. In terms of Islamic law, the pillars of grants include the giver ( wahib ), recipient ( mauhub lahu ), the donated goods ( mauhub ), and the valid ijab kabul. Thus, the grant and alms are not only sunnah practices recommended in Islam, but also play a strategic role in creating community welfare.